2022
DOI: 10.1002/nop2.1498
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of young people living with type 1 diabetes and their caregivers about its management

Abstract: Aims and Objective:We sought to investigate knowledge and skills of type 1 diabetes (T1D) management among young people living with the disease and their caregivers.Our aim is to provide baseline evidence to inform T1D self-management education for young people living with the disease and their caregivers.Background: Both local and international guidelines recommend ongoing T1D selfmanagement education for people living with the disease. This is because T1D often develops among young people who rarely have the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Nutrition literacy involves the ability of individuals to obtain, process, understand, and apply nutrition information and services they need to make appropriate nutrition decisions (Consavage Stanley et al, 2022 ). Poor nutrition literacy have been linked to poor health outcomes (Owusu et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nutrition literacy involves the ability of individuals to obtain, process, understand, and apply nutrition information and services they need to make appropriate nutrition decisions (Consavage Stanley et al, 2022 ). Poor nutrition literacy have been linked to poor health outcomes (Owusu et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…This was indicated in another study. 28 The study findings revealed that self-management practices among the respondents were as follows: only 22.2% had good problem-solving skills, 29.9% had healthy coping skills, 46.2% were able to practice healthy eating, 67.4% were compliant with medications, 65.6% were able to practice risk reduction behaviors, 53.4% were able to monitor their blood sugar daily whereas 43.4% were physically active. The study found that many children and adolescents with type 1 diabetes (T1D) in the study area were not effectively managing their condition.…”
Section: Discussionmentioning
confidence: 92%
“…However, there appeared to be no moderation of posts to evaluate the quality of the information provided by forum users or to remove irrelevant/incorrect information. Other studies have described the use of information sources, such as online fora, by patients and their carers when looking for answers to questions about their medical conditions 35,36 . However, this may suggest that carers are not being provided with sufficient information from HCPs regarding the availability of pharmacological and nonpharmacological management options and local services and support to which they could be signposted, 12 leading them to look elsewhere for advice.…”
Section: Discussionmentioning
confidence: 99%